2017
DOI: 10.1177/1010428317694303
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree and BRCA gene analysis in breast cancer patients to identify hereditary breast and ovarian cancer syndrome to prevent morbidity and mortality of disease in Indian population

Abstract: Global burden of breast cancer is expected to increase to >2 million new cases every year by 2030 and 10% of these are likely to have hereditary breast and ovarian cancer syndrome. Identifying these individuals by pedigree and BRCA1/2 mutation analyses will enable us to offer targeted mutation testing and appropriate counseling. This study from a tertiary care hospital showed that of the 127 breast cancer patients on treatment during 2014-2015, 24 of them fulfilled the criteria of hereditary breast and ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
0
18
0
2
Order By: Relevance
“…However, despite the high penetrance and the high frequency of variants found in BRCA1/BRCA2 genes, only about 20% of hereditary BC and OC have been attributed to the presence of pathogenic variants in those genes, moreover, about 5-10% have been associated with other susceptibility genes, such as TP53, STK11, PTEN, ATM, and CHEK2 [14]. Studies have demonstrated molecular diagnosis rates of about 4.6-54% when only BRCA1/BRCA2 are screened, which evidences the association of other less penetrant genes with HBOC pathogenesis [15][16][17][18]. Even though the protocols for clinical management are well established for BRCA1/BRCA2 carriers, patients tested negative for pathogenic BRCA1/BRCA2 variants lack the proper clinical follow-up and genetic counselling when presenting similar clinical characteristics and BC/OC increased risk [19].…”
Section: Introductionmentioning
confidence: 94%
“…However, despite the high penetrance and the high frequency of variants found in BRCA1/BRCA2 genes, only about 20% of hereditary BC and OC have been attributed to the presence of pathogenic variants in those genes, moreover, about 5-10% have been associated with other susceptibility genes, such as TP53, STK11, PTEN, ATM, and CHEK2 [14]. Studies have demonstrated molecular diagnosis rates of about 4.6-54% when only BRCA1/BRCA2 are screened, which evidences the association of other less penetrant genes with HBOC pathogenesis [15][16][17][18]. Even though the protocols for clinical management are well established for BRCA1/BRCA2 carriers, patients tested negative for pathogenic BRCA1/BRCA2 variants lack the proper clinical follow-up and genetic counselling when presenting similar clinical characteristics and BC/OC increased risk [19].…”
Section: Introductionmentioning
confidence: 94%
“…The advantage of identifying a family with higher risk of hereditary cancers are: [30,31] a. Identification of which members of cancer has that risk and more importantly which member of the family does not have this risk.…”
Section: Hereditary Cancersmentioning
confidence: 99%
“…Yet, it is important to screen and test for hereditary cancer risk in select groups of families -to tailor the screening, diagnosis, treatment, and follow-up recommendations for those with higher risk. [30][31][32]…”
Section: Individuals Have Different Levels Of Coping Ability Andmentioning
confidence: 99%
See 2 more Smart Citations